Urqensi keberadaan Komisi Pengawasan Kepolisian Ditinjau Dari Hukum Administrasi Negara - Nurmin K. Martam (Universitas Negeri Gorontalo, 2009)
In practice, many police actions categorized as arbitrary action of w ich is not based on duty and function of police institute as arranged in tugirtotion applied. Be awate of arbitrary action done by policement, goverment provides potting to every public or citizen to report the arbitrary action to national policement commision. National policement Commission basically undertakes gives observation to all business or activity about implementation of duty or police activity that matching with the one which is expected. Kata Kunci: Urgensi. Komisi Pengawasan, Kepolisian, Hukum administrasi